Broad Street, Barbados. - Co. Ltd, Robert MacLehose Glasgow (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
A busy picture of Broad Street, Bridgetown in Barbados. An officer can be seen under a shade directing traffic, several cars on both sides of the street as many pedestrians go about their day. Businesses in the photo are The Canadian Bank of Commerce, Knights and Johnson’s Stationery. Info. At the back: CTP £18 STAMP: 4 cents Barbados Postage Stamp Copyright: Barbados Publicity Committee Printed in Scotland by Robert Maclehose & Co. Ltd., Glasgow Yes Mac! I am in Barbados and I hope it’s for good. We didn't like Canada one bit. You have no doubt already seen what the.... have said about ‘Sylvia’. Best of luck to you and ....." Edgan "D. Mc Gibney .... 22 Hamilton Road, Bromley, Kent. England.
Landscape, black & white, 4 x 6 in., divided back
Keywords: Buildings; Banks; Cars; Vehicles; People; Pedestrians; Stores and shops; Cityscapes; Transportation; Buildings; Architectural elements; Business enterprises; Police; Traffic police; City and town life; Knights (Pharmacy); Canadian Bank of Commerce; Johnson's Stationery